MiRNA-146a rs2910164 Confers a Susceptibility to Digestive System Cancer: A Meta-Analysis Involving 59,098 Subjects - Lv, Lu; Gu, Haiyong; Chen, Zheng; Tang, Weifeng; Zhang, Sheng; Lin, Zhaoxian (Immunological investigations, 2022)
MicroRNA (miR)-146a might participate in the occurrence of malignant tumor. The aim of the current investigation was to evaluate the relationship of microRNA-146a (miR-146a) rs2910164 C > G locus to the development of digestive system cancer (DSC). We retrieved publications from PubMed, China Biology Medicine and EMBASE databases up to August 29, 2019. Finally, 56 independent case-control studies with 59,098 participants were included. The strength of the relationship between rs2910164 locus and a risk of DSC was assessed. The power value was also calculated in this study. We identified a correlation of rs2910164 locus in miR-146a with DSC development in dominant model (P = .035; power value = 0.994). MiR-146a rs2910164 locus was also identified to be correlated with a risk of DSC in Asians (GG/CG vs. CC: P = .033; power value = 0.989). Sensitivity analysis revealed that any individual study could not alter the final decision. In our study, no significant bias was found among these included studies (P > .1). The results of heterogeneity analysis suggested that small sample size (<1000 subjects), colorectal carcinoma, Asians, gastric carcinoma, esophageal squamous cell carcinoma, hepatocellular cancer, hospital-based study and high-quality score (≥7.0) subgroups contributed the heterogeneity to our findings. Galbraith radial plot determined that eleven outliers contributed to the main heterogeneity. In summary, this meta-analysis highlights that rs2910164 locus might be implicated in the risk of DSC. More studies are, therefore, needed to confirm our results.